الوساطة الجنائية وامكانية تطبيقها في التشريع العماني - Mohammed Rashid Ahmed Al-Makhmari
This research aims to discuss criminal mediation and its possible implementation in Omani law through a descriptive-analytical research. The researchers divided the study into five chapters. First, an introductory chapter where the researcher explains the preamble to the study such as problem statement, objectives, methodology and others. In the second chapter the Researcher has explained the essence, characteristics, and types of mediation. The third chapter discusses the rules of criminal mediation, which cover the limitations of the conditions of execution, scope, procedures, and their influence on criminal proceedings, as well as the evaluation of the criminal mediation system. In the fourth chapter the researchers examine the implementation of criminal mediation in comparative legislation. In the fifth and final chapter, researchers discuss the possible implementation and applicability of criminal mediation in Omani legislation. The problem statement of the study arises when too many criminal cases are referred to the public prosecutor, a large number of which are small cases. This situation has distracted the courts from dealing with more important cases. To reduce the burden of Public Prosecutors, Judges and save time and money, researchers are looking for the possibility of implementing criminal mediation in Omani law. In the process of collecting data, researchers have used a descriptive (inductive) approach. While in the analytical process the researcher uses the method of information analysis. This study has produced several findings, namely that criminal mediation is an alternative to avoid criminal prosecution and satisfy the disputing parties by discussing under the supervision of a third party, known as a mediator. Criminal mediation also has judicial and social features in resolving disputes amicably and peacefully. The study also found that criminal mediation proceedings require legal permission, there is an application to the public prosecutor or court, the consent of the disputing parties to negotiate and agreement on compensation to the victim of the crime. The study also concludes that comparative legislations implementing criminal mediation differ in limiting the crimes that can be solved through criminal mediation. The study also found that the different laws that adopt criminal mediation differ in their definition of criminal offenses that permit criminal mediation. Even so, they do not go beyond two criteria: restrictive and general principle. In most laws, a successful criminal mediation means that the criminal proceeding has ended; such is the conduct of criminal proceeding for the implementation of modern criminal policy. The study has proposed several recommendations, especially to Omani lawmakers and generally to Arab legislators, that they must observe criminal mediation in a deeper and more serious manner, and to consider it as a modern and unconventional method of resolving criminal disputes. This way, they can resolve the criminal justice crisis that has plagued many Arab countries due to the increasing number of cases before the courts, and the dissatisfaction and injustice felt by the disputing parties. The study also suggests universities to introduce a new course in the faculty of law to teach alternative methods of resolving criminal disputes, especially criminal mediation. By doing so, they can introduce the concept, rules, procedures, and impacts of criminal mediation. The study also specifically suggests Omani lawmakers to adopt delegated mediation and the restrictive and general principle criteria to define criminal offences that can be resolved using criminal mediation.